Variables Affecting the Extraction of Antioxidants in Cold and Hot Brew Coffee: A Review - Brian G. Yust; Frank Wilkinson; Niny Z. Rao (MDPI AG, 2023)
Coffee beans are a readily available, abundant source of antioxidants used worldwide. With the increasing interest in and consumption of coffee beverages globally, research into the production, preparation, and chemical profile of coffee has also increased in recent years. A wide range of variables such as roasting temperature, coffee grind size, brewing temperature, and brewing duration can have a significant impact on the extractable antioxidant content of coffee products. While there is no single standard method for measuring all of the antioxidants found in coffee, multiple methods which introduce the coffee product to a target molecule or reagent can be used to deduce the overall radical scavenging capacity. In this article, we profile the effect that many of these variables have on the quantifiable concentration of antioxidants found in both cold and hot brew coffee samples. Most protocols for cold brew coffee involve an immersion or steeping method where the coffee grounds are in contact with water at or below room temperature for several hours. Generally, a higher brewing temperature or longer brewing time yielded greater antioxidant activity. Most studies also found that a lower degree of coffee bean roast yielded greater antioxidant activity.